Characterization of 65 epitope-specific dystrophin monoclonal antibodies in canine and murine models of duchenne muscular dystrophy by immunostaining and western blot. - Kasun Kodippili; Lauren Vince; Jin-Hong Shin; Yongping Yue; Glenn E Morris; Mark A McIntosh; Dongsheng Duan (PLoS ONE, 2014)
Epitope-specific monoclonal antibodies can provide unique insights for studying cellular proteins. Dystrophin is one of the largest cytoskeleton proteins encoded by 79 exons. The absence of dystrophin results in Duchenne muscular dystrophy (DMD). Over the last two decades, dozens of exon-specific human dystrophin monoclonal antibodies have been developed and successfully used for DMD diagnosis. Unfortunately, the majority of these antibodies have not been thoroughly characterized in dystrophin-deficient dogs, an outstanding large animal model for translational research. To fill the gap, we performed a comprehensive study on 65 dystrophin monoclonal antibodies in normal and dystrophic dogs (heart and skeletal muscle) by immunofluorescence staining and western blot. For comparison, we also included striated muscles from normal BL10 and dystrophin-null mdx mice. Our analysis revealed distinctive species, tissue and assay-dependent recognition patterns of different antibodies. Importantly, we identified 15 antibodies that can consistently detect full-length canine dystrophin in both immunostaining and western blot. Our results will serve as an important reference for studying DMD in the canine model.